Heterocycle amide isosteres: An approach to overcoming resistance for HIV-1 integrase strand transfer inhibitors. Issue 3 (1st February 2020) - Peese, Kevin M.; Naidu, B. Narasimhulu; Patel, Manoj; Li, Chen; Langley, David R.; Terry, Brian; Protack, Tricia; Gali, Volodymyr; Lin, Zeyu; Samanta, Himadri K.; Zheng, Ming; Jenkins, Susan; et al.
Graphical abstract: Abstract: A series of heterocyclic pyrimidinedione-based HIV-1 integrase inhibitors was prepared and screened for activity against purified integrase enzyme and/or viruses modified with the following mutations within integrase: Q148R, Q148H/G140S and N155H. These are mutations that result in resistance to the first generation integrase inhibitors raltegravir and elvitegravir. Based on consideration of drug-target interactions, an approach was undertaken to replace the amide moiety of the first generation pyrimidinedione inhibitor with azole heterocycles that could retain potency against these key resistance mutations. An imidazole moiety was found to be the optimal amide substitute and the observed activity was rationalized with the use of calculated properties and modeling. Rat pharmacokinetic (PK) studies of the lead imidazole compounds demonstrated moderate clearance and moderate exposure.